№11) 0,6х²у(-0,5х⁵у⁷)= - 0,3х⁷y⁸2) 0,6x⁴(-10x⁴)³ = - 6x⁴x¹²= - 6x¹⁶3) (8a⁴+2a³) : (
а³)=
4) (3a² - 11a + 4) - (6a² - 2a - 3) = 3a² - 11a +4 - 6a² + 2a +3 = -3a² - 9a +75) (x+1)(x² - 3x - 4) = x³ - 3x² - 4x + x² - 3x - 4 = x³ - 2x² - 7x - 4№2.1) (x-4)(x-5) - 2x(x-6) = x² - 5x - 4x +20 - 2x² +12x = - x² + 3x +202) (2a +3x)(5a - x) - (a+x)(10a - 3x) = 10a² - 2ax + 15ax - 3x² - (10a² -3ax +10ax - 3x²) = 10a² +13ax - 3x² - 10a² - 7ax + 3x² = 6ax№3.1) (3x+2)(2x - 1) - 3x(2x+3) + 2x при х= - 0,4Сначала упростим исходное выражение:(3x+2)(2x - 1) - 3x(2x+3) + 2x = 6x² - 3x +4x - 2 - 6x² - 9x +2x= - 6x - 2Теперь вместо х подставим -0,4:-6*(-0,4) - 2=2,4-2=0,4№4.1) 2x+
Ответ: х= - 1,752) (4х+1)(х+5) - (2x+1)(2x - 3) = 584x²+20x+x+5 - (4x² - 6x +2x -3) = 584x²+21x+5 - 4x² +4x+3 = 5825x = 58-825x = 50x=50:25x=2Ответ: х=2